The Single-Molecule Long-Read Sequencing of Intestine After Soy Meal-Induced Enteritis in Juvenile Pearl Gentian Grouper, Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂ - Zhang, Wei; Tan, Beiping; Deng, Junming; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Liu, Hongyu; Zhang, Shuang; Xie, Shiwei; Zhang, Haitao (Frontiers in Marine Science, 2021)
Intestinal inflammatory disease induced by excessive soy protein substitutions for fish meal (FM) protein is a common phenomenon. The pearl gentian grouper, Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂, a marine fish with important economical and nutritional values, exhibited a similar problem. As far as we know, there are no reports on the full-length transcriptome of the pearl gentian grouper. In the present study, seven isonitrogenous and isolipidic (10% lipid) diets were prepared and fed to fish for 10 weeks. The water volume in each barrel was about 1 m3, using natural light and temperature. The results showed that 40% dietary soy proteins significantly negatively affected the growth performance of the pearl gentian grouper. Compared to the FM control, the content of immunoglobulin M and the enzyme activities of glutathione reductase, glutathione peroxidase, and total superoxide dismutase in the intestine significantly increased; the content of malondialdehyde in the intestine significantly decreased; and the enzyme activities of alanine transaminase and aspartate transaminase in the liver significantly increased. A library composed of seven different treated distal intestine tissues, including the FM control group, 20% soybean meal substitute for FM (SBM20), SBM40, 20% soybean protein concentrate (SPC20), SPC40, 20% fermented soybean meal substitute for FM (FSBM20), and FSBM40, was constructed and sequenced using PacBio single-molecule real-time (SMRT) and the RNA-Seq technology. As a whole, this study obtained 420,006 full-length non-chimeric (FLNC) reads. After error correction, sequence clustering, and redundancy, 82,351 transcripts with high quality were obtained. In addition, a total of 77,815 transcripts were annotated in seven databases (non-redundant protein sequences, non-redundant nucleotide sequences, Protein family, Clusters of Orthologous Groups of proteins, Gene Ontology, Swiss-Prot, and KEGG Orthology). Also, 49,093 long non-coding RNAs (lncRNAs) and 141,702 simple sequence repeats were identified. Based on full-length transcriptome sequencing, the present study found that the Toll-like receptor/nuclear factor kappa-B signaling pathway plays an important role in the development of SBM- and FSBM-induced enteritis. SPC-induced enteritis is mainly accompanied by a general imbalance of the nutrition absorption-related signaling pathways, which only affects a small part of the immune-related signaling pathways. This study supplies new and valuable reference transcripts, which would better facilitate further research on the pearl gentian grouper.